High flame-retardant composite shielding material and preparation method thereof
Patent Information
- Application Number
- CN202611082195.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-13
AI Technical Summary
现有技术难以平衡屏蔽、阻燃与力学三项核心性能,因此,亟需发明一种兼具高屏蔽、高阻燃和高力学强度的屏蔽材料,以满足核辐射防护复合材料技术领域的更高需求
1、本发明通过将粗、细两种铅粉混合填充,提高了堆积密度,在保证屏蔽效果的同时,减少了对材料韧性的破坏,
Smart Images

Figure REF-OBJ-1784613191302-000001 
Figure REF-OBJ-1784613191302-000002
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nuclear radiation protection composite materials technology, specifically, it relates to a high flame-retardant composite shielding material and its preparation method. Background Technology
[0002] With the rapid development and widespread application of nuclear energy technology, the research and development of high-performance composite shielding materials has become an important research direction in the field of materials science. Lead-boron-polyethylene composite shielding materials, due to their excellent neutron / gamma-ray synergistic shielding ability, good processability, and strong corrosion resistance, are widely used in key areas such as nuclear power plant shielding layers, nuclear fuel transport containers, medical accelerator rooms, and radiation protection bulkheads of nuclear submarines. These materials typically use polyethylene as the matrix, lead powder as the gamma-ray shielding filler, boron carbide as the neutron absorbing filler, and flame retardants to impart flame-retardant properties, thus achieving a multi-functional integrated design.
[0003] However, lead-boron-polyethylene composite shielding materials have long faced a significant technical bottleneck in practical engineering applications. To achieve high shielding effectiveness and high flame retardancy, a large amount of functional fillers needs to be added to the material, resulting in an extremely high total filler content. While this high filler content effectively ensures shielding and flame retardancy, it significantly degrades the material's mechanical properties. Existing technologies struggle to balance the three core properties of shielding, flame retardancy, and mechanical strength. Therefore, there is an urgent need to invent a shielding material that combines high shielding, high flame retardancy, and high mechanical strength to meet the higher demands of the nuclear radiation protection composite materials technology field. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide a high flame-retardant composite shielding material and its preparation method.
[0005] The objective of this invention can be achieved through the following technical solutions: A high flame-retardant composite shielding material comprises the following raw materials in parts by weight: 90-100 parts polyethylene resin, 315-350 parts lead powder, 10-30 parts boron carbide, 20-30 parts flame retardant, 4-10 parts coupling agent, 3-8 parts dispersant and 0.5-2 parts antioxidant.
[0006] Preferably, the lead powder includes coarse lead powder and fine lead powder, with a mass ratio of 1:1.
[0007] Preferably, the coarse lead powder has an average particle size of 25-35 μm, and the fine lead powder has an average particle size of 2-8 μm.
[0008] Preferably, the coupling agent is a silane coupling agent.
[0009] Preferably, the dispersant is a stearate dispersant.
[0010] Preferably, the antioxidant is a phenolic antioxidant.
[0011] Preferably, the flame retardant is prepared by the following steps: S1. In a round-bottom flask (equipped with a stirrer), add 3,5-dihydroxybenzaldehyde, 2-aminothiazole and 1,4-dioxane in sequence. Heat in an oil bath to 80-85℃ and stir for 2-3 hours. After the reaction is complete, the Schiff base product is obtained after post-processing. S2. In a three-necked round-bottom flask (equipped with a stirrer, reflux condenser and nitrogen inlet), add the Schiff base product, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), toluene and triethylamine in sequence. Start stirring and introduce nitrogen gas. Heat in an oil bath to 110-115℃ and reflux for 6-8 hours. After the reaction is complete, the DOPO adduct is obtained after post-treatment. S3. In a round-bottom flask (equipped with a stirrer), add DOPO adduct, potassium carbonate, potassium iodide (catalyst) and N,N-dimethylformamide in sequence. Stir to suspend most of the solids, then slowly add 1-chlorooctane dropwise. After the addition is complete, heat the oil bath to 90-95°C and stir the reaction for 6-8 hours. After the reaction is complete, the flame retardant is obtained after post-treatment.
[0012] Preferably, the ratio of 3,5-dihydroxybenzaldehyde to 2-aminothiazole in step S1 is 13.8g:10.0g.
[0013] Preferably, in step S2, the ratio of the Schiff base product to 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 22.0 g: 21.6 g.
[0014] Preferably, the ratio of the amount of DOPO adduct to 1-chlorooctane in step S3 is 43.6 g: 32.6-33.1 g.
[0015] In the above preparation process, in order to ensure the smooth progress of the reaction, in step S3, the molar ratio of DOPO adduct to 1-chlorooctane needs to be controlled to be close to 1:2, and the latter should be in excess.
[0016] The reaction formula for preparing the flame retardant according to this invention is as follows:
[0017] As can be seen from the above reaction formula, the flame retardant prepared by this invention introduces a thiazole ring and a DOPO group into its molecule. During combustion, the P group of the DOPO group pyrolyzes to generate phosphorus-containing free radicals, which capture H· and HO· free radicals in the gas phase, interrupting the combustion chain reaction. The thiazole ring simultaneously contains both N and S flame-retardant elements. While providing synergistic flame-retardant performance, the S element can also capture free radicals generated by high-energy radiation (neutrons / gamma rays), indirectly improving the aging resistance of the shielding material. Finally, the introduced long-chain alkyl group enhances the interfacial bonding force between the flame retardant and PE, effectively relaxing the internal stress generated during hot pressing and preventing the material from becoming brittle due to excessive rigidity. Therefore, compared to inorganic flame retardants, the flame retardant prepared by this invention requires less dosage and achieves superior flame-retardant performance while maintaining mechanical properties.
[0018] This invention also provides a method for preparing a highly flame-retardant composite shielding material, comprising the following steps: A1. Place lead powder and boron carbide in a drying oven to dry them and remove surface moisture. Then put them into a high-speed mixer and premix for 3-5 minutes to initially disperse the powder. A2. Mix the coupling agent with the ethanol aqueous solution, stir to dissolve, and then spray into a high-speed mixer. At the same time, turn on the heating and raise the temperature to 90-95℃. Stir and mix for 20-30 minutes. A3. Raise the temperature of the high-speed mixer to 125-130℃, increase the speed, add the dispersant to the mixer, and stir for 20-30 minutes. A4. Stop heating the high-speed mixer, reduce the speed, and then add polyethylene resin, flame retardant and antioxidant in sequence. Continue mixing for 20-30 minutes to obtain the mixture. A5. After hot pressing the mixture into the mold, cool and open the mold to obtain a high flame-retardant composite shielding material.
[0019] Preferably, the drying temperature is 100-105℃ and the drying time is 3-5 hours.
[0020] Preferably, the hot pressing temperature is 190-200℃, the pressure is 20MPa, and the time is 20-30min.
[0021] The beneficial effects of this invention are: 1. This invention increases the packing density by mixing coarse and fine lead powders, thus reducing damage to the material's toughness while ensuring the shielding effect. 2. This invention provides a self-made flame retardant containing phosphorus, nitrogen, and sulfur. It not only requires a small amount and has a good flame retardant effect, but also captures free radicals generated by radiation, thereby improving the anti-aging ability of the material. 3. The long-chain structure of the flame retardant makes it more compatible with the plastic matrix, reducing internal stress during processing and preventing the material from cracking due to excessive rigidity. In summary, the shielding material prepared by this invention achieves a good balance between shielding performance, flame retardant performance, and mechanical properties, and has important application value in the field of nuclear radiation protection composite materials technology. Detailed Implementation
[0022] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0023] Example 1 Preparation of flame retardants: S1. In a round-bottom flask (equipped with a stirrer), add 27.6 g of 3,5-dihydroxybenzaldehyde, 20 g of 2-aminothiazole and 100 mL of 1,4-dioxane in sequence. Heat in an oil bath to 80 °C and stir for 2 h. When the reaction is complete, filter the reaction solution quickly with a Buchner funnel while it is hot. Collect the filtrate and evaporate it by rotary evaporation to remove most of the solvent. Let it stand in a refrigerator overnight to precipitate a large amount of crystals. Collect the crystals by filtration, wash with anhydrous ethanol, and dry to obtain the Schiff base product. S2. In a three-necked round-bottom flask (equipped with a stirrer, reflux condenser and nitrogen inlet), add 33g of Schiff base product, 32.4g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 150mL of toluene and 1g of triethylamine in sequence. Start stirring and introduce nitrogen gas. Heat in an oil bath to 110℃ and reflux for 6h. When the reaction is complete, filter the reaction solution while hot and collect the filtrate. Rotary evaporate the filtrate to remove most of the solvent. Purify by column chromatography (eluent is petroleum ether / ethyl acetate, volume ratio is 3:1) to obtain the DOPO adduct. S3. In a round-bottom flask (equipped with a stirrer), add 43.6 g of DOPO adduct, 48.3 g of potassium carbonate, 1.6 g of potassium iodide, and 200 mL of N,N-dimethylformamide in sequence. Stir to suspend most of the solids, then slowly add 32.6 g of 1-chlorooctane. After the addition is complete, heat the mixture in an oil bath to 90 °C and stir for 6 h. Once the reaction is complete, cool the reaction solution to room temperature, filter, collect the filtrate, and evaporate the filtrate by rotary evaporation to remove most of the solvent. Purify the filtrate by column chromatography (eluting with petroleum ether / ethyl acetate = 6:1 to 4:1, gradient elution) to obtain the flame retardant.
[0024] A method for preparing a high flame-retardant composite shielding material includes the following steps: A1. Place 315 parts of lead powder (coarse lead powder and fine lead powder in a mass ratio of 1:1, with an average particle size of 25 μm for coarse lead powder and 2 μm for fine lead powder) and 10 parts of boron carbide (average particle size of 10 μm) in a drying oven and dry at 100°C for 3 hours to remove surface moisture. Then, put them into a high-speed mixer (300 rpm) for 3 minutes to premix and disperse the powder initially. A2. Mix 4 parts of silane coupling agent KH-550 with 30 parts of ethanol aqueous solution (ethanol to water mass ratio of 4:1), stir to dissolve, spray into a high-speed mixer (speed 1200 rpm), turn on the heater at the same time, heat to 90℃, stir and mix for 20 minutes. A3. Raise the temperature of the high-speed mixer to 125°C and increase the speed (1800 rpm). Add 3 parts of zinc stearate to the mixer and stir for 20 minutes. A4. Stop heating the high-speed mixer, reduce the speed (500 rpm), and then add 90 parts of polyethylene resin, 20 parts of flame retardant and 0.5 parts of antioxidant 1010 in sequence. Continue mixing for 20 minutes to obtain the mixture. A5. The mixture is poured into the mold and hot-pressed at 190℃ and 20MPa for 20 minutes. After cooling, the mold is opened to obtain a high flame-retardant composite shielding material.
[0025] Example 2 Preparation of flame retardants: S1. In a round-bottom flask (equipped with a stirrer), add 27.6 g of 3,5-dihydroxybenzaldehyde, 20 g of 2-aminothiazole and 100 mL of 1,4-dioxane in sequence. Heat in an oil bath to 85 °C and stir for 3 h. When the reaction is complete, filter the reaction solution quickly with a Buchner funnel while it is hot. Collect the filtrate and evaporate it by rotary evaporation to remove most of the solvent. Let it stand in a refrigerator overnight to precipitate a large amount of crystals. Collect the crystals by filtration, wash with anhydrous ethanol, and dry to obtain the Schiff base product. S2. In a three-necked round-bottom flask (equipped with a stirrer, reflux condenser and nitrogen inlet), add 33g of Schiff base product, 32.4g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 150mL of toluene and 1g of triethylamine in sequence. Start stirring and introduce nitrogen gas. Heat in an oil bath to 115℃ and reflux for 8 hours. After the reaction is complete, filter the reaction solution while hot and collect the filtrate. Rotary evaporate the filtrate to remove most of the solvent. Purify by column chromatography (eluent is petroleum ether / ethyl acetate, volume ratio is 3:1) to obtain the DOPO adduct. S3. In a round-bottom flask (equipped with a stirrer), add 43.6 g of DOPO adduct, 48.3 g of potassium carbonate, 1.6 g of potassium iodide, and 200 mL of N,N-dimethylformamide in sequence. Stir to suspend most of the solids, then slowly add 33.1 g of 1-chlorooctane. After the addition is complete, heat the mixture in an oil bath to 95 °C and stir for 8 h. Once the reaction is complete, cool the reaction solution to room temperature, filter, collect the filtrate, and evaporate the filtrate by rotary evaporation to remove most of the solvent. Purify the filtrate by column chromatography (eluting with petroleum ether / ethyl acetate = 6:1 to 4:1, gradient elution) to obtain the flame retardant.
[0026] A method for preparing a high flame-retardant composite shielding material includes the following steps: A1. Place 330 parts of lead powder (coarse lead powder and fine lead powder in a mass ratio of 1:1, with an average particle size of 35 μm for coarse lead powder and 8 μm for fine lead powder) and 20 parts of boron carbide (average particle size of 20 μm) in a drying oven and dry at 105℃ for 5 hours to remove surface moisture. Then, put them into a high-speed mixer (300 rpm) for 5 minutes to premix and disperse the powder. A2. Mix 7 parts of silane coupling agent KH-550 with 35 parts of ethanol aqueous solution (ethanol to water mass ratio of 4:1), stir to dissolve, spray into a high-speed mixer (speed 1200 rpm), turn on the heater at the same time, heat to 95℃, stir and mix for 30 min. A3. Raise the temperature of the high-speed mixer to 130°C and increase the speed (2000 rpm). Add 5.5 parts of zinc stearate to the mixer and stir for 30 minutes. A4. Stop heating the high-speed mixer, reduce the speed (500 rpm), and then add 95 parts of polyethylene resin, 25 parts of flame retardant and 1.0 part of antioxidant 1010 in sequence. Continue mixing for 30 minutes to obtain the mixture. A5. The mixture is poured into the mold and hot-pressed at 200℃ and 20MPa for 30 minutes. After cooling, the mold is opened to obtain a high flame-retardant composite shielding material.
[0027] Example 3 The only difference between this embodiment and Embodiment 1 is that, in this embodiment, a method for preparing a high flame-retardant composite shielding material includes the following steps: A1. Place 350 parts of lead powder (coarse lead powder and fine lead powder in a mass ratio of 1:1, with an average particle size of 35 μm for coarse lead powder and 8 μm for fine lead powder) and 30 parts of boron carbide (average particle size of 20 μm) in a drying oven and dry at 105℃ for 5 hours to remove surface moisture. Then, put them into a high-speed mixer (300 rpm) for 5 minutes to premix and disperse the powder. A2. Mix 10 parts of silane coupling agent KH-550 with 40 parts of ethanol aqueous solution (ethanol to water mass ratio of 4:1), stir to dissolve, spray into a high-speed mixer (speed 1200 rpm), turn on the heater at the same time, heat to 95℃, stir and mix for 30 min. A3. Raise the temperature of the high-speed mixer to 130°C and increase the speed (2000 rpm). Add 8 parts of zinc stearate to the mixer and stir for 30 minutes. A4. Stop heating the high-speed mixer, reduce the speed (500 rpm), and then add 100 parts of polyethylene resin, 30 parts of flame retardant and 2 parts of antioxidant 1010 in sequence. Continue mixing for 30 minutes to obtain the mixture. A5. The mixture is poured into the mold and hot-pressed at 200℃ and 20MPa for 30 minutes. After cooling, the mold is opened to obtain a high flame-retardant composite shielding material.
[0028] Comparative Example 1 The only difference between this comparative example and Example 1 is that in this comparative example, an equal amount of DOPO was used to replace the flame retardant to obtain the material.
[0029] Comparative Example 2 The only difference between this comparative example and Example 1 is that the lead powder used in this comparative example is coarse lead powder.
[0030] The following performance tests were performed on Examples 1, 2, and 3, and Comparative Examples 1 and 2: Vertical combustion rating was determined using the GB / T 2408-2021 standard. Tensile strength was determined according to GB / T 1040.2-2022 standard; use 137 A Cs radioactive source (0.662 MeV, gamma rays) was used, along with a multichannel gamma spectrometer and a 10 mm sample thickness. Gamma photon counts were measured with and without a sample, and the attenuation rate was calculated as follows: Gamma attenuation rate = (blank count - sample count) / blank count × 100% The measurement results are shown in Table 1: Table 1
[0031] As can be seen from the measurement results in Table 1, the shielding material prepared by the embodiments of the present invention achieves a good balance between shielding performance, flame retardant performance and mechanical properties. Therefore, the present invention has important application value in the field of nuclear radiation protection composite materials technology.
[0032] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
Claims
1. A high flame-retardant composite shielding material, characterized in that, The raw materials include the following parts by weight: 90-100 parts polyethylene resin, 315-350 parts lead powder, 10-30 parts boron carbide, 20-30 parts flame retardant, 4-10 parts coupling agent, 3-8 parts dispersant and 0.5-2 parts antioxidant.
2. The high flame-retardant composite shielding material according to claim 1, characterized in that, The flame retardant is prepared by the following steps: S1. In a flask, add 3,5-dihydroxybenzaldehyde, 2-aminothiazole and 1,4-dioxane in sequence, heat to 80-85℃, stir for 2-3 hours until the reaction is complete, and obtain the Schiff base product. S2. In a flask, add the Schiff base product, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, toluene and triethylamine in sequence. Start stirring and purge with nitrogen. Heat to 110-115°C and reflux for 6-8 hours. Once the reaction is complete, the DOPO adduct is obtained. S3. In a flask, add DOPO adduct, potassium carbonate, potassium iodide and N,N-dimethylformamide in sequence, stir, then add 1-chlorooctane dropwise. After the addition is complete, heat to 90-95℃ and stir to react for 6-8 hours. The reaction is complete, and the flame retardant is obtained.
3. The high flame-retardant composite shielding material according to claim 2, characterized in that, In step S1, the ratio of 3,5-dihydroxybenzaldehyde to 2-aminothiazole is 13.8 g: 10.0 g.
4. The high flame-retardant composite shielding material according to claim 2, characterized in that, In step S2, the ratio of the Schiff base product to 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 22.0 g: 21.6 g.
5. The high flame-retardant composite shielding material according to claim 2, characterized in that, In step S3, the ratio of DOPO adduct to 1-chlorooctane is 43.6 g: 32.6-33.1 g.
6. The high flame-retardant composite shielding material according to claim 1, characterized in that, The lead powder includes coarse lead powder and fine lead powder, with a mass ratio of 1:
1.
7. The high flame-retardant composite shielding material according to claim 1, characterized in that, The coupling agent is a silane coupling agent, the dispersant is a stearate dispersant, and the antioxidant is a phenolic antioxidant.
8. A method for preparing a high flame-retardant composite shielding material, used to prepare the high flame-retardant composite shielding material according to any one of claims 1-7, characterized in that, Includes the following steps: A1. Dry the lead powder and boron carbide, then put them into a mixer and premix for 3-5 minutes; A2. Mix the coupling agent with the ethanol aqueous solution, stir to dissolve, spray into the mixer, turn on the heating at the same time, raise the temperature to 90-95℃, and stir to mix for 20-30 minutes. A3. Raise the temperature of the mixer to 125-130℃, increase the speed, add the dispersant to the mixer, and stir for 20-30 minutes; A4. Stop heating the high-speed mixer, reduce the speed, and then add polyethylene resin, flame retardant and antioxidant in sequence. Continue mixing for 20-30 minutes to obtain the mixture. A5. After hot pressing the mixture into the mold, cool and open the mold to obtain a high flame-retardant composite shielding material.
9. The method for preparing a high flame-retardant composite shielding material according to claim 8, characterized in that, The hot pressing temperature is 190-200℃ and the time is 20-30 minutes.